Average Error: 0.0 → 0.0
Time: 18.4s
Precision: 64
• ## could not determine a ground truth for program body (more)

1. x = 1.3100436170095023e+65
$\sinh \left(x + 1\right) - \sinh x$
$\left(\cosh x \cdot \sinh 1 + \cosh 1 \cdot \sinh x\right) - \sinh x$
\sinh \left(x + 1\right) - \sinh x
\left(\cosh x \cdot \sinh 1 + \cosh 1 \cdot \sinh x\right) - \sinh x
double f(double x) {
double r9110690 = x;
double r9110691 = 1.0;
double r9110692 = r9110690 + r9110691;
double r9110693 = sinh(r9110692);
double r9110694 = sinh(r9110690);
double r9110695 = r9110693 - r9110694;
return r9110695;
}


double f(double x) {
double r9110696 = x;
double r9110697 = cosh(r9110696);
double r9110698 = 1.0;
double r9110699 = sinh(r9110698);
double r9110700 = r9110697 * r9110699;
double r9110701 = cosh(r9110698);
double r9110702 = sinh(r9110696);
double r9110703 = r9110701 * r9110702;
double r9110704 = r9110700 + r9110703;
double r9110705 = r9110704 - r9110702;
return r9110705;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\sinh \left(x + 1\right) - \sinh x$
2. Using strategy rm
3. Applied sinh-sum0.0

$\leadsto \color{blue}{\left(\sinh x \cdot \cosh 1 + \cosh x \cdot \sinh 1\right)} - \sinh x$
4. Final simplification0.0

$\leadsto \left(\cosh x \cdot \sinh 1 + \cosh 1 \cdot \sinh x\right) - \sinh x$

# Reproduce

herbie shell --seed 1
(FPCore (x)
:name "sinh(x+1)-sinh(x)"
(- (sinh (+ x 1.0)) (sinh x)))